Comprehensive molecular tumor profiling in radiation oncology: How it could be used for precision medicine. Issue 1 (1st November 2016) - Eke, Iris; Makinde, Adeola Y.; Aryankalayil, Molykutty J.; Ahmed, Mansoor M.; Coleman, C. Norman
Highlights: Tumor cell resistance to chemoradiation and targeted drugs affects patient outcome. Novel techniques can be used to stratify patients and predict therapy efficacy. Radiation can modulate target expression and improve efficacy of targeted therapy. Development of personalized treatment strategies enables precision medicine. Abstract: New technologies enabling the analysis of various molecules, including DNA, RNA, proteins and small metabolites, can aid in understanding the complex molecular processes in cancer cells. In particular, for the use of novel targeted therapeutics, elucidation of the mechanisms leading to cell death or survival is crucial to eliminate tumor resistance and optimize therapeutic efficacy. While some techniques, such as genomic analysis for identifying specific gene mutations or epigenetic testing of promoter methylation, are already in clinical use, other "omics-based" assays are still evolving. Here, we provide an overview of the current status of molecular profiling methods, including promising research strategies, as well as possible challenges, and their emerging role in radiation oncology.